Pengaruh Edukasi Gizi Melalui Media Booklet terhadap Perubahan Pilihan Makanan Camilan pada Remaja di Makassar - Andi Sri Rahayu Kasma (Universitas Sulawesi Barat, 2022)
Snacking activity has been identified as one of the potential causes of obesity and/or overweight in childhood and adolescence. According to Hampl, a child is snacking more than 15-20% of his daily calorie intake of snacks can be defined as